BIODESULFURIZATION OF SIMULATED LIGHT FUEL OIL BY A NATIVE ISOLATED BACTERIA BACILLUS CEREUS HN - Asghar Molaee Dehkordi; D. Arabian; H. Najafi; F. Farhadi (Journal of Petroleum Science and Technology, 2014)
In the present paper, the biodesulfurization of simulated light fuel oil (i.e., dibenzothiophene (DBT) in dodecane) and untreated kerosene with a high total sulfur content has been studied by a native isolated bacterium named Bacillus cereus HN. The influences of various parameters such as the reaction temperature (T), biocatalyst cell density, oil phase fraction (OFP), and initial DBT concentration on the fractional conversion of the model sulfur compound were investigated. The experimental data obtained were used to determine the reaction rate constant of the model sulfur compound and the corresponding activation energy. Furthermore, the biodesulfurization of un-treated kerosene with a total sulfur content of 2333 ppmw produced by an Iranian refinery company (Isfahan refinery) was investigated to examine the capability of this new microorganism. It was realized that about 33% of the total sulfur content of untreated kerosene could be removed after 72 hrs. The results of the response surface methodology (RSM) showed that a quadratic correlation could be proposed for the influences of biocatalyst cell density, OFP, and initial DBT concentration on the desulfurization of DBT.